Tomato Plant Proteins Actively Responding to Fungal Applications and Their Role in Cell Physiology - Bashir, Zoobia; Shafique, Sobiya; Ahmad, Aqeel; Shafique, Shazia; Yasin, Nasim A.; Ashraf, Yaseen; Ibrahim, Asma; Akram, Waheed; Noreen, Sibgha (Frontiers in Physiology, 2016)
The pattern of protein induction in tomato plants has been investigated after the applications of pathogenic and nonpathogenic fungal species. Moreover, particular roles of the most active protein against biological applications were also determined using chromatographic techniques. Alternaria alternata and Penicillium oxalicum were applied as a pathogenic and nonpathogenic fungal species, respectively. Protein profile analysis revealed that a five protein species (i.e. protein 1, 6, 10, 12 and 13) possessed completely coupled interaction with nonpathogenic inducer application (P. oxalicum). However, three protein species (i.e. 10, 12 and 14) recorded a strong positive interaction with both fungal species. Protein 14 exhibited the maximum interaction with fungal applications, and its role in plant metabolism was studied after its identification as protein Q9M1W6. It was determined that protein Q1M1W6 was involved in guaiacyl lignin biosynthesis, and its inhibition increased the coumarin contents in tomato plants. Moreover, it was also observed that the protein Q9M1W6 takes significant part in the biosynthesis of jasmonic acid and Indole acetic acid contents, which are defense and growth factors of tomato plants. The study will help investigators to design fundamental rules of plant proteins affecting cell physiology under the influence of external fungal applications.